PENGARUH TERPAAN KONTEN INFLUENCER INSTAGRAM TERHADAP MOTIVASI MELAKUKAN ONLINE SELF DISCLOSURE (Survei Pada Pengikut Akun Instagram @catwomanizer) - Fitria Nissa Zahara, - (2020)
Self-disclosure on social networks began to appear at the time of the presence of computer mediated communication (CMC), especially when social media began to become a trend, one of which was Instagram. Instagram, with its various features, is the social media that has the highest triggers for its users to make public self-disclosures. Not only from the use of social media, there are also other factors that can trigger users to self-disclose, namely the effect of media exposure, which in the context of this study influencer content. As users who have massive followers, influencers can move and influence their followers with very high feedback through the content they upload on personal accounts, therefore a lot of users in this case are followers of the' accounts influencers who often make self-disclosures, on their respective social media. The purpose of this study was to determine how significant the influence of Instagram Influencer's content exposure (X) has on the motivation to conduct online self-disclosure (Y). The method used is quantitative correlational with a questionnaire distribution simple random sampling technique to 100 respondents who are followers of the @catwomanizer Instagram account. The results showed that the two variables simultaneously had a degree of relationship of 0.620 with a strong level of correlation.